Indexing in an Actor-Oriented Database - Bernstein, Phil; Dashti, Mohammad; Kiefer, Tim; Maier, David (Conference on Innovative Database Research (CIDR), 2017)
Many of today’s interactive server applications are implemented using actor-oriented programming frameworks. Such applications treat actors as a distributed in-memory object-oriented database. However, actor programming frameworks offer few if any database system features, leaving application developers to fend for themselves. It is challenging to add such features because the design space is different than traditional database systems. The system must be scalable to a large number of servers, it must work well with a variety of cloud storage services, and it must integrate smoothly with the actor programming model. We present the vision of an actor-oriented database. We then describe one component of such a system, to support indexed actors, focusing especially on details of the fault tolerance design. We implemented the indexing component in the Orleans actor- oriented programming framework and present the result of initial performance measurements.